Applying the integrated behavioural model to identify predictors of utilisation of state-funded health insurance in Khyber Pakhtunkhwa province, Pakistan - Junaid Ur Rehman Siddiqui; Waqas Hameed; Mahnoor Fatima; Shifa Salman Habib; Kiran Sohail Azeemi; Ali Hussaini; Asma Altaf Hussain Merchant; Adil Haider; Sameen Siddiqi (Journal of the Pakistan Medical Association, 2024)
Objective: To utilize the integrated behavioural model (IBM) for identifying predictors of utilization of state-funded health insurance in Khyber-Pakhtunkhwa province, Pakistan. Methods: Using a cross-sectional design, the household survey was conducted across ten districts of the KP province during Nov 22-Feb 23 which included a total of 1750 households. Exploratory factor analysis (EFA) and confirmatory factor analysis (CFA) were used to identify and validate the emerging factors, respectively. Structural equation modelling (SEM) was used to validate the causal relationships in the final model. Results: Six factors were identified through EFA namely, Perception of Financial Protection, Perceived Benefits around Sehat Card Plus Programme (SCP-P), Perceived Norm around SCP-P, Personal Agency to use SCP-P, Intention to use SCP-P, and Knowledge of SCP-P. Factors’ reliability and validity were established using CFA with coefficients > 0.7.The final structural model yielded a good fit with a Root Mean Squared Error of Approximation (RMSEA) <0.06 and Comparative Fit Index (CFA) >0.97. Perception of financial protection (B=-0.3) is inversely related to how people viewed the benefits of using SCP. In other words, the more people feel financially protected, the fewer benefits they see in the SCP-P. People's intention to use SCP in the future was mostly influenced by two factor: first, whether they felt using SCP was the norm (B= 0.6) or expected behaviour in the society like by friends and family, and second, whether they believed using SCP would be beneficial (B= 0.5). People's actual use of SCP in the past year was dependant on intention to use the programme (B=0.2), their knowledge as to how much they know about it (B=0.2), and their personal ability or control over using it (B=0.3). Conclusion: The analyses guide SCP-P’s communication and engagement strategy, emphasizing that programme efforts should focus on promoting positive perceptions and norms surrounding SCP, highlighting its benefits, providing education and information to enhance knowledge about SCP, and empowering individuals with a sense of personal agency to improve SCP utilization in the province. Keywords: Integrated Behavioural Model (IBM), Health Insurance Utilization. Behaviour Model Validation, Structural Equation Modelling (SEM), Perception of Financial Protection.